New species of Cyphocharax (Characiformes: Curimatidae) from the upper rio Negro, Amazon basin - Melo,Bruno F. (2014)
A new species of Cyphocharax, Curimatidae, apparently endemic to the blackwater upper rio Negro of the Amazon basin in northern Brazil, is described.The new species is readily distinguished from its congeners by the presence of a distinctly longitudinally elongate, posteriorly vertically expanding patch of dark pigmentation along the midlateral surface of the caudal peduncle, with the patch extending from the base of the middle caudal-fin rays anteriorly past the vertical through the posterior terminus of the adipose fin. The new species additionally differs from all congeners in details of body and fin pigmentation and meristic and morphometric ratios. Evidence for the assignment of the species to Cyphocharax and the occurrence of other species of the Curimatidae apparently endemic to the upper rio Negro catchment is discussed.